Effects of Electroacupuncture Preconditioning at Baihui and Zusanli Acupoints on the Expression of Inflammatory Factors in Brain and Intestines of Rats with Cerebral Ischemia/Reperfusion - ZHANG Jiyao; TANG Qiang; ZHU Luwen (康复学报)
ObjectiveTo observe the effects of electroacupuncture preconditioning on the expression of interleukin-17A（IL-17A）and IL-10 in the brain and intestine of rats with cerebral ischemia/reperfusion and to explore the brain-gut protective effect of electroacupuncture preconditioning.MethodsA total of 36 male Sprague-Dawley rats were randomly divided into the sham group (S-con group), the model group (M-con group), and the electroacupuncture preconditioning group (EP group) ,with 12 cases in each group. The S-con group was operated according to the model of middle cerebral artery occlusion/reperfusion (MCAO/R) with no blocking of the cerebral blood flow and reperfusion. The M-con group was given the operation of MCAO/R model and the cerebral blood perfusion was restored after 120 minutes. The EP group was intervened by electroacupuncture preconditioning at Baihui (DU20) and Zusanli (ST36) acupoints for two weeks, and was given the operation of MCAO/R model after the last electroacupuncture intervention for 24 hours, the cerebral blood perfusion was restored after 120 minutes. Before surgery for one day, after reperfusion for 12 h and after reperfusion for 1,3,7 days, the grip tester was used to measure the forelimb grasping strength; after reperfusion for 7 days, ELISA methods was used to determine the content of IL-17A and IL-10 in serum, Western blot method was used to detect the expression of IL-17A and IL-10 protein in ischemic cortex and colon tissue, immunohistochemistry method was used to calculate the average optical density (AOD) value of IL-17A and IL-10 in ischemic cortex and colon tissue, and HE staining method was used to observe the pathological change of ischemic cortex.Results① Forelimb grasping strength: compared with the S-con group, the forelimb grasping strength of rats in the M-con group after reperfusion for 12 h, 1 d, 3 d, 7 d was decreased significantly (P<0.05); compared with the M-con group, the forelimb grasping strength of rats in the EP group was increased significantly (P<0.05). ② Content of IL-17A and IL-10 in serum: after reperfusion for 7 days , compared with the S-con group, the content of serum IL-17A and IL-10 of rats in the M-con group were significantly increased (P<0.05); compared with the M-con group, the content of serum IL-17A in the EP group were significantly decreased (P<0.05), and IL-10 in the EP group were significantly increased (P<0.05). ③ Expression of IL-17A and IL-10 protein: after reperfusion for 7 days, compared with the S-con group, the expression of IL-17A and IL-10 protein in ischemic cortex and colon tissue in the M-con group were significantly increased (P<0.05); compared with the M-con group, the expression of IL-17A in the EP group was significantly decreased (P<0.05), and the expression of IL-10 protein in the EP group was significantly increased (P<0.05). ④ AOD value of IL-17A and IL-10: after reperfusion for 7 days, compared with the S-con group, the AOD value of IL-17A and IL-10 in ischemic cortex and colon tissue in the M-con group were significantly increased (P<0.05); compared with the M-con group, the AOD value of IL-17A in the EP group was significantly decreased (P<0.05), the AOD value of IL-10 in the EP group was significantly increased (P<0.05). ⑤ Pathological change of ischemic cortex: after reperfusion for 7 days, compared with the M-con group, the pathological change of ischemic cortex in EP group was significantly decreased (P<0.05).ConclusionElectroacupuncture preconditioning at Baihui and Zusanli acupoints can reduce the pathological damage degree of the ischemic cortex and intestinal-central inflammation, improve neurobehavioral function, which may be related to brain-gut protection.